(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Notazioni introduttive - 2. I termini della vicenda da cui origina il rinvio pregiudiziale e la competenza della Corte di giustizia a pronunziarsi sulla questione controversa - 3. La portata applicativa del regolamento n. 1259 del 2010 e le sentenze dei tribunali religiosi - 4. Le implicazioni di carattere sistematico della pronunzia in rapporto al principio di incompetenza dell’Unione nella materia ecclesiastica o religiosa - 5. I dubbi sostanziali circa la riconoscibilità in Europa del ripudio islamico - 6. Conclusioni. The issue of the civil recognizability of the Islamic divorce by the EU Court of Justice (considerations on the ruling of December 20th 2017, C-372/16) ABSTRACT: The present paper takes as a starting point a recent ruling by the EU Court of Justice concerning the issue of recognizability of Islamic repudiation under the EU Regulation No. 1259/2010. After assessing the conditions underlying the jurisdiction of the Court of Justice to rule on such a controversial matter, the Author excludes that the religious judgments fall within the scope of the aforementioned regulation (and within the purpose of Regulation No. 2201/2013), also in light of the so-called principle of the Union’s incompetence in ecclesiastical or religious matters. Moreover, although the unilateral repudiation is to be considered contrary to the principle of public order of the moral and legal equality of the spouses, the Author concludes that, consistently with the current trend of many legal systems to give increasing broader space to the “negotiating” management of the marriage bond, effective protection of the principle of equality should involve letting women, in some particular situations, have the choice of concretely enforcing that principle.